Pengaruh Senam Nifas terhadap Penyembuhan Luka Perineum Derajat II pada Ibu Post Partum di BPM Murtinawita Kota Pekanbaru - Mella Roza; Juraida Roito Hrp; Zuchrah Hasan (Jurnal Forum Kesehatan, 2018)
Second degree perineal lacerations are a discomfort or inconvenience for postpartum mothers and can increase morbidity and incidence of infection. A preliminary survey conducted at PMB Murtinawita showed that 7 out of 10 postpartum mothers had Second degree perineal lacerations so that it could cause disruption and discomfort for the mother after delivery. Perineal tear can heal faster by doing postpartum exercise, resulting in contraction and relaxation of the pelvic muscles thus helping to alleviate disinfecting the perineum as well as improving local circulation, reducing edema, and accelerating the healing of tear. This study aimed to determine the average and the influence of postnatal exercise on healing of Second degree perineal lacerations. The research was conducted in September 2017-May 2018. The population was all normal postpartum mothers in PMB Murtinawita with a sample size of 22 taken by purposive sampling method, with 11 in each group. The results showed that the average healing of the perineal wound in the intervention group was 5.91 days and in the control group was 6.82 days. Man-Whitney statistical test results showed that there was influence of postpartum exercise on healing of second degree perineal lacerations with p-value 0.001. It is suggested to midwives to make postpartum exercise program in accordance with the guides through maternal visits